Disclosure of Diagnosis and Treatment Among Early Stage Prostate Cancer Survivors - Jackson, Trent (2009)
OBJECTIVE: Increased long-term survival rates have led to a greater focus on the health-related quality of life (HRQL) of prostate cancer survivors. This study assessed the motivations of prostate cancer survivors for disclosing their diagnosis and treatment to close others, and their perceptions of their own and others’ responses to the disclosure. METHODS: Prostate cancer survivors (N = 35) who were 24–36 months post-treatment for localized disease completed a semi-structured telephone interview. Open-ended questions concerning disclosure of men’s diagnosis and treatment and their perceptions of their own and others’ reactions to the disclosure were included. RESULTS: Regarding men’s motivations for disclosing their diagnosis and treatment, men reported that they were seeking social support (SS) and that others had a ‘right to know.’ Further, the receipt of emotional support and feeling a sense of positive emotions were common following disclosure about their diagnosis and treatment. Participants reported continuing to discuss their treatment side effects 2–3 years post–treatment. CONCLUSION: Prostate cancer survivors reported an overall positive and supportive response following the disclosure of their diagnosis and treatment. Further examination of the relationship between SS and HRQL will be necessary to identify interventions to enhance the well-being of this growing population of survivors. PRACTICE IMPLICATIONS: Providers need to be aware of the extent and long-term nature of the side effects following treatment for prostate cancer. If providers encourage men to talk about their diagnosis, treatment, and side effects, providers may better understand men’s experience with the disease, and men may be more likely to accept these commonly experienced changes, as well as seek treatment for them. These efforts may result in improved quality of life for survivors of prostate cancer